2022
DOI: 10.1155/2022/5109638
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Optimization of Aesthetic Education Teaching Information Platform Based on Big Data Analysis

Abstract: In the process of promoting school aesthetic education, some schools have some problems, such as insufficient construction of campus aesthetic education environment, lack of aesthetic thinking in various disciplines, and so on. In view of these problems, combined with the concept of the flipped classroom and the characteristics of artificial intelligence task-driven teaching, taking PHP, HTML + CSS + JS, and other development technologies as the main development technologies, and relying on the flipped classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To cultivate well-rounded professionals oriented towards internationalization, digitalization, and sustainable development, universities are continuously deepening practical teaching reforms through measures such as encouraging faculties to apply for grants relevant to teaching reform, establishing collaborative experimental teaching bases between the university and enterprise, and building joint training platforms for innovative talents [1][2][3][4][5][6][7][8][9][10]. Our team has collaborated with ELANE, a Beijing-based company specializing in shipping data, to develop a green shipping monitoring experimental platform based on fundamental knowledge and representative data.…”
Section: Introductionmentioning
confidence: 99%
“…To cultivate well-rounded professionals oriented towards internationalization, digitalization, and sustainable development, universities are continuously deepening practical teaching reforms through measures such as encouraging faculties to apply for grants relevant to teaching reform, establishing collaborative experimental teaching bases between the university and enterprise, and building joint training platforms for innovative talents [1][2][3][4][5][6][7][8][9][10]. Our team has collaborated with ELANE, a Beijing-based company specializing in shipping data, to develop a green shipping monitoring experimental platform based on fundamental knowledge and representative data.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%